Oral health and obesity in the SAYCARE study: reliability and internal validity of diagnostic methods - M. P. M. Rando‐Meirelles; M. L. R. Sousa; G. C. Vale; V. A. Lages; P. P. Vásquez; P. Jimenez; R. S. Villena; M. A. Alvarez‐Paucar (Wiley, 2019)
Summary Objective The aim of this pilot study was to address the reliability, internal validity and viability of oral health methods used in the South American Youth/Child cARdiovascular and Environmental study. Methods South American Youth/Child cARdiovascular and Environmental study was a multicentre feasibility observational study and conducted in seven South American cities. The training sessions were performed in two steps before data collection: the first verified the inter‐rater reproducibility between the examiners of the six centres in relation to the gold standard, and the second one verified the inter‐rater reproducibility between the examiners at each centre in relation to the main rater. The diagnostic methods used were International Caries Detection and Assessment System II and Pulpal Involvement, Ulceration, Fistula and Abscess for dental caries and Periodontal Screening and Recording and Index Plaque for periodontal disease. Anthropometric variables were measured and used to calculate the body mass index and were classified according to the cut‐off points defined by the International Obesity Task Force. Cohen's kappa coefficient and proportions of agreement were calculated to report inter‐rater and intra‐rater reliability in the calibration process and pilot study. Results The inter‐rater weight kappa ranged from 0.78 to 0.88 and proportion of agreement from 96.07% to 98.10% for the International Caries Detection and Assessment System II and for the Periodontal Screening and Recording, 0.68 to 0.95 and 94.40% to 98.33%, respectively, in the calibration process. At the pilot study, a total of 490 children (40.8% overweight and 12.9% obese) and 364 adolescents (23.4% overweight and 4.3% obese) were examined. The prevalence of dental caries was 66% in children and 78% in adolescents, and gingival bleeding was 49% and 58.20%, respectively. Conclusion The results demonstrated good reliability and internal validity after the examiners were trained, as well as the feasibility of using the methods chosen for this multicentre study.